Performance of Various Length-to-Diameter Ratio of Thermal Energy Storage Tank: A Convergence Test - Fouzi, M.S.A.; Amin, N.A.M.; Mohamad, A.; Mohamad, M.S.; Basha, M.H.; Rahman, A.A.; Bakar, M.S.; Karim, M.A.; Zaman, I. (International Journal of Integrated Engineering, 2024)
Thermal Energy Storage (TES) is a technique that stores thermal energy, accomplished by changing the temperature of a storage medium, such as a phase change material (PCM), for later use in various applications, for example, heating and cooling or power generation. The heat energy that is saved is usually kept in the storage medium. This study investigates how the performance of the TES tank is affected by the ratio of length to diameter. The research focuses on how the ratio affects the convergence test while the PCM0 (water-ice) used in TES starts to release latent heat into the air. Five models were designed by using CATIA software and the analysis was conducted in ANSYS CFD software. Convergence tests were conducted to validate the accuracy of the obtained simulation results. Two additional criteria, namely temperature and ice mass fraction, were also analysed to evaluate the performance of the TES tanks. The investigation of the TES tank using five different models has shown that each model reaches a constant temperature of 0°C during the melting phase, but at different time intervals. Model 1 reaches this temperature the fastest, followed by Model 2, Model 3, Model 4, and finally Model 5. A model that reached the constant temperature first indicated a more efficient discharging process, as it signified a faster rate of ice melting and thermal energy release. In terms of ice mass fraction, Model 1 retained a significant amount of solid ice (0.9968), with noticeable melting. Model 5, on the other hand, showed minimal melting and better preservation of solid ice (0.9992). Considering temperature, ice mass fraction and ease of convergence, Model 1 performed the best, when the solidified PCM0 was melting faster while maintaining a substantial amount of solid ice in the TES tank. The present study was successfully developed and compared various TES configurations while satisfying the convergence criteria set in the simulation. To conclude with, the results showcase the performance differences based on pipe size. These discoveries contribute to refining tube-type TES tanks and their design for thermal energy storage systems.